(untitled) (Philological Studies, 2019)
The article deals with the “otherness” in A.Trollope’s “Nina Balakka”. The representations of European culture of 19th century Prague is under analysis. Trollope mixes the British and European culture to arrange a “distance game” between the reader and the characters. Discovering Prague with its cultural, historical and linguistic peculiarities reader allows himself to feel the collision of the novel more acutely and to sympathize with the characters more.